1992
DOI: 10.1159/000261424
|View full text |Cite
|
Sign up to set email alerts
|

Noncariogenicity of Maltitol in Specific Pathogen-Free Rats Infected with Mutans Streptococci

Abstract: The effect of maltitol on caries development was examined in an experimental caries system employing specific pathogen-free (SPF) Sprague-Dawley rats. Fourteen strains of oral streptococci, including mutans streptococci, did not utilize the maltitol nor produce sufficient acid to demineralize tooth enamel. Furthermore, maltitol did not serve as a substrate for glucosyltransferases of either Streptococcus mutans MT8148R or Streptococcus sobrinus 6715 to synthesize water-insoluble glucan. Maltitol induced no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
(13 reference statements)
0
13
0
1
Order By: Relevance
“…Evaluation of maltitol in vivo by the pH response of dental plaque using an intra-oral apparatus 31 and in vivo by experimental enamel demineralisation 81 has demonstrated that maltitol does not lower plaque pH 80 . It has also been demonstrated that 14 strains of oral streptococci, including mutans streptococci, do not utilise maltitol or produce sufficient acid in its presence to demineralise tooth enamel 82 . Furthermore, maltitol does not serve as a substrate for glucosyltransferases of either S.mutans MT8148R or S.mutans 6715 for the synthesis of water-insoluble glucan 82 .…”
Section: Maltitol <4-o-alpha-d-glucopyranosyl-d-glucitol C 12 H 24 Omentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of maltitol in vivo by the pH response of dental plaque using an intra-oral apparatus 31 and in vivo by experimental enamel demineralisation 81 has demonstrated that maltitol does not lower plaque pH 80 . It has also been demonstrated that 14 strains of oral streptococci, including mutans streptococci, do not utilise maltitol or produce sufficient acid in its presence to demineralise tooth enamel 82 . Furthermore, maltitol does not serve as a substrate for glucosyltransferases of either S.mutans MT8148R or S.mutans 6715 for the synthesis of water-insoluble glucan 82 .…”
Section: Maltitol <4-o-alpha-d-glucopyranosyl-d-glucitol C 12 H 24 Omentioning
confidence: 99%
“…It has also been demonstrated that 14 strains of oral streptococci, including mutans streptococci, do not utilise maltitol or produce sufficient acid in its presence to demineralise tooth enamel 82 . Furthermore, maltitol does not serve as a substrate for glucosyltransferases of either S.mutans MT8148R or S.mutans 6715 for the synthesis of water-insoluble glucan 82 . A significantly lower caries score was also reported for rats fed maltitol compared with those fed sucrose 82 .…”
Section: Maltitol <4-o-alpha-d-glucopyranosyl-d-glucitol C 12 H 24 Omentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement of sucrose with maltitol in the diet resulted in a trend towards caries reduction. 37 More recently, Mäkinen and co-workers compared the effects of erythritol, a tetritol (4-carbon sugar alcohol), with xylitol and D-glucitol (a 6-carbon sugar alcohol) on the risk of dental caries. 38 The use of erythritol and xylitol resulted in a statistically significant reduction in the plaque and saliva levels of S. mutans (p <0.001 in most cases) and there was also a significant reduction in the amount of dental plaque in groups receiving erythritol and xylitol.…”
Section: Caries Reduction With Other Polyolsmentioning
confidence: 99%
“…최근에는 구강내에서효과적인 항충치 작용을 가진 소재를 발굴하기 위해서 1) St. mutans의 증식을 저해하는 작용 [4,5] 2) sucrose로부터 glucan형성에 관여하는 GTase활성 저해 작용 [6,7], 3) St. mutans가 대사하지 못하는 sucrose대체 감미료 사용 등 천연물질로부터 항충치 물질을 분리하고자 하는 연구가 시도되었다 [8].…”
unclassified